2016
DOI: 10.1186/s12957-016-0909-2
|View full text |Cite
|
Sign up to set email alerts
|

Rare occurrence of metastasis from lung cancer to the anus: case report and review of the literature

Abstract: BackgroundAnal metastases from lung cancer are infrequent, and there are only 10 published cases. Life expectancy is no longer than 1 year after diagnosis because of the typically advanced stage of disease. Treatment, which is typically inefficient, is administered with the intent to cure or avoid local complications.Case presentationWe report a case of a patient with non-small cell lung cancer presenting with perianal metastasis mimicking an abscess.ConclusionsBecause perianal masses may be misdiagnosed, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…Owing to several limitations associated with early stage diagnosis, majority of lung cancer patients diagnosed at the median or advanced stage. Additionally, due to the moderate progress provided by chemotherapeutics and the development of drug resistance 1,2 , the use of natural products for lung cancer treatment has attracted the attention 5 . In this study, chemical examination of Phoma sp .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to several limitations associated with early stage diagnosis, majority of lung cancer patients diagnosed at the median or advanced stage. Additionally, due to the moderate progress provided by chemotherapeutics and the development of drug resistance 1,2 , the use of natural products for lung cancer treatment has attracted the attention 5 . In this study, chemical examination of Phoma sp .…”
Section: Discussionmentioning
confidence: 99%
“…The major lung cancer NSCLC includes various types such as squamous cell carcinoma, large cell carcinoma, adenocarcinoma, pleomorphic, carcinoid tumor, and salivary gland carcinoma 1 . The metastasis-related death found to be as high as 90% of all lung cancer mortality 2 . Despite advances in conventional treatment procedures such as surgery, radiation, chemotherapy and targeted therapy, however, the clinical outcomes of the current therapies are still not at satisfactory level.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Metastatic lung cancer has been known to be highly malignant, and has been noted to have spread to any location, from the oral cavity to the anus. [10] Liu et al [11] reported that in the 64 documented cases, 57 patients displayed metastasis. The jejunum was the most common site, as noted in 50.9% (29/57) of patients, followed by the ileum, in 33.3% (19/57), and the duodenum, in 15.8% (9/57).…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective study done by Kim et al[ 5 ] gastrointestinal metastasis was found in 0.19% of all the cases with small bowel being the most common site, although autopsy studies revealed higher rates of metastatic disease[ 1 ]. Metastatic lung cancer has known to spread to any location from the oral cavity to the anus[ 6 ] with lymphatic and hematogenous routes being the possible modes of spread[ 7 ].…”
Section: Discussionmentioning
confidence: 99%